2020
DOI: 10.5935/1518-0557.20190065
|View full text |Cite
|
Sign up to set email alerts
|

First custom next-generation sequencing infertility panel in Latin America: design and first results

Abstract: Objective: To present the development of the first custom gene panel for the diagnosis of male and female infertility in Latin America.Methods: We developed a next-generation sequencing (NGS) panel that assesses genes associated with infertility. The panel targeted exons and their flanking regions. Selected introns in the CFTR gene were also included. The FMR1 gene and Y chromosome microdeletions were analyzed with other recommended methodologies. An inhouse developed bioinformatic pipeline was applied for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 49 publications
0
8
0
1
Order By: Relevance
“…The elevated number of candidate genes makes it hard to find a genetic cause of infertility in the majority of the cases (22)(23)(24). Anyway, a multi-disease gene panel can improve the identification of the etiology of male infertility (3,25,26). In several cases, idiopathic infertility has a genetic origin, therefore a correct phenotyping and medical history of the infertile patient may represent an initial basis for the genetic interpretation of the disorder (27), especially for the genetic variants of uncertain Severe oligozoospermia was defined for total sperm count <1.0 million; mild oligozoospermia was defined for total sperm count enclosed between 1.0 and 5.0 million; oligozoospermia for total sperm count enclosed between 5.0 and 39.0 million (21).…”
Section: Discussionmentioning
confidence: 99%
“…The elevated number of candidate genes makes it hard to find a genetic cause of infertility in the majority of the cases (22)(23)(24). Anyway, a multi-disease gene panel can improve the identification of the etiology of male infertility (3,25,26). In several cases, idiopathic infertility has a genetic origin, therefore a correct phenotyping and medical history of the infertile patient may represent an initial basis for the genetic interpretation of the disorder (27), especially for the genetic variants of uncertain Severe oligozoospermia was defined for total sperm count <1.0 million; mild oligozoospermia was defined for total sperm count enclosed between 1.0 and 5.0 million; oligozoospermia for total sperm count enclosed between 5.0 and 39.0 million (21).…”
Section: Discussionmentioning
confidence: 99%
“…Some examples also have been illustrated in the development of infertility NGS panel for targeted exons and their flanking regions in 75 infertility related genes, including FSHR as one of the diagnostic genes which have proven associations with infertility, in order to assess the genetic variations of infertile patients with a custom bioinformatic pipeline for data analysis. By applying the MiSeq platform of Illumina, investigators revealed the underlying genetic cause of infertility in their 25 samples properly [ 56 ]. França et al also reviewed the ability of NGS methods in the discovery of heterogeneity of some FSHR and other infertility gene-related disorders and concluded the widespread usage of such technologies in the near future for the detection of new players in female reproduction diseases would be recommended [ 57 ].…”
Section: Advanced Genetic Screening Methods For Fshr Profilingmentioning
confidence: 99%
“…To investigate if rare variants potentially involved in the development of OHSS were present, variants called in the 12 cases with OHSS were filtered using a predefined in silico gene panel including 76 genes predisposing to OHSS (Online Resource 2). The genes included in the gene panel were selected based on an extensive literature search in PubMed and Online Mendelian Inheritance in Man (OMIM) and were implicated in controlled ovarian stimulation response, associated with OHSS or regulation of gonadotropin action and/or ovarian angiogenesis [3,14,[16][17][18][19][20][21][22][23][24]. The gene panel included both known disease-associated genes related to OHSS and candidate genes which association with OHSS needs further study.…”
Section: Analysis I: In Silico Gene Panelmentioning
confidence: 99%